Manajemen Pendidikan Dalam Moderasi Beragama Di Era Disrupsi Digital - Kadek Hengki Primayana; Putu Yulia Angga Dewi (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
Management is a process carried out to achieve an organization's goals by working in teams and an application of management has a subject and an object. Education is a learning effort and learning process for students to actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves and society. Educators and education personnel in the educational process play a strategic role, especially in efforts to shape the character of the nation through the development of the desired personality and values. Viewed from the educational dimension, the role of educators in Indonesian society remains dominant even though the technology that can be utilized in the learning process is developing very quickly. Likewise, their education staff is tasked with carrying out administration, management, development, supervision and technical services to support the educational process in educational units.